Acupuncture improves neurological function and anti-inflammatory effect in patients with acute ischemic stroke: A double-blinded randomized controlled trial - Chueh-Yi Tsai; Wen-Ling Liao; Hung-Ming Wu; Chia-Wei Chang; Wei-Liang Chen; Ching-Liang Hsieh (Elsevier, 2024)
Background and purpose: Acupuncture exerts an anti-inflammatory effect and is recommended by the World Health Organization as a complementary therapy for stroke. This study investigated the improvement in neurological function outcome in acute-stage intervention of acute ischemic stroke (AIS), and the anti-inflammatory effect of early acupuncture. Methods: Fifty patients with AIS were randomly assigned to either a control group (CG, 25 patients, received sham acupuncture) or treatment group (TG, 25 patients, received acupuncture treatment). Acupuncture intervention was administered twice a week for a total of 8 sessions over 4 consecutive weeks. The primary outcome was the changes in the National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), and Barthel Index (BI) scores. The secondary outcome was the changes in serum inflammation-related biomarker levels.(ANAIS trial) Results: A total of 35 patients (18 patients in the CG and 17 patients in the TG) completed the trial. The reduction in NIHSS scores was greater in the TG than in the CG between V2 (second assessment administered after acupuncture intervention) and V1 (first assessment administered before acupuncture intervention; 4.33 ± 1.91 vs. 2.68 ± 1.42, p = 0.005) and between V3 (third assessment administered 28 days after last acupuncture intervention) and V1 (6.00 ± 2.53 vs. 3.83 ± 2.31, p = 0.012). The increase in BI scores was greater in the TG than in the CG between V2 and V1 (28.89 ± 15.39 vs. 14.21 ± 19.38, p = 0.016) and between V3 and V1 (39.41 ± 20.98 vs. 25.00 ± 18.47, p = 0.038). Among participants with high inflammation, the increase in serum IL-12p70 level between V2 and V1 was greater in the TG than in the CG (0.20 ± 0.19 vs. −0.14 ± 0.30, pg/mL p = 0.006). Conclusions: Acupuncture improved the neurological function of patients with AIS, and the relationship between acupuncture improving neurological function and anti-inflammatory effect needs further study. In addition, studies with larger sample sizes and longer follow-ups as well as multicenter clinical trials are expected in the future.